Haptoglobin testing in hemolysis: Measurement and interpretation. Issue 4 (5th March 2014) - Shih, Andrew W.Y.; McFarlane, Andrew; Verhovsek, Madeleine
<x xml:space="preserve">Abstract</x> Haptoglobin is primarily produced in the liver and is functionally important for binding free hemoglobin from lysed red cells in vivo, preventing its toxic effects. Because haptoglobin levels become depleted in the presence of large amounts of free hemoglobin, decreased haptoglobin is a marker of hemolysis. Despite its ubiquity and importance, a paucity of literature makes testing difficult to interpret. This review highlights the many physiological roles that have been recently elucidated in the literature. Different methodologies have been developed for testing, including spectrophotometry, immunoreactive methods, and gel electrophoresis. These are covered along with their respective advantages and disadvantages. As there is no single gold standard for hemolysis, validation studies must rely on a combination of factors, which are reviewed in this article. Pitfalls and limitations of testing are also addressed. False positives can occur in improper specimen preparations, cirrhosis, elevated estrogen states, and hemodilution. False negatives can occur in hypersplenism and medications such as androgens and corticosteroids. Haptoglobin testing in the setting of inflammation is additionally discussed as interpretation can be difficult in this setting. Given the widespread use of haptoglobin testing, it is vital that clinicians and laboratory staff understand the principles and correct interpretation of this test. Am. J. Hematol. 89:443–447, 2014. © 2013 Wiley Periodicals, Inc.